Freirean Perspectives on Environmental Education amidst the Climate Emergency - Saito, Carlos Hiroo; Germanos, Erika (International Journal of Environmental Resilience Research and Science, 2024)
Abstract: The Intergovernmental Panel on Climate Change (IPCC) warns that climate-related risks will intensify, necessitating urgent climate actions. Despite the global risk and urgency, responses to the climate emergency, even when acknowledged, often end up reinforcing social discrimination, affirming that the concept of risk is associated with social inequality. It is argued that environmental education can confront these challenges, counter climate denialism, promote awareness, and empower communities to actively engage in sustainable practices through the Freirean approach. This paper presents a theoretical framework for Freirean Environmental Education in the Climate Emergency. Paulo Freire's dialogical-problematizing approach is linked to the concept of vulnerability, ensuring that Freirean environmental education leads to transformative actions. The entire conceptual and methodological structure is described through a flowchart. Vulnerability to the climate emergency and actions to address it should be developed at the local level, allowing limit-situations and the participatory or exclusionary process can be codified for educational purposes. A Canadian and a Brazilian case study are briefly discussed in light of this educational proposal. Key Words: Paulo Freire. Climate justice. Vulnerability. Canada. Brazil.